Dampak Current Ratio Dan Debt To Equity Ratio Pada Return Saham Dimoderasi Return On Assets - Martinus Robert Hutauruk; Siti Rohmah; Sandi Dharmawan (JAS (Jurnal Akuntansi Syariah), 2022)
This study aims to show empirical evidence through analysis of the impact of the current ratio (CR) and debt to equity ratio (DER) on stock returns, return on assets (ROA) being moderated in automotive and component sub-sector companies listed on the Indonesia Stock Exchange (IDX) in 2017-2020. This study used a sample of 11 automotive and parts industries listed on the IDX with eight issuers holding sharia shares. The sampling technique uses purposive sampling. Data analysis used linear regression and moderated regression analysis (MRA). This study confirms that CR and ROA positively impact stock returns. However, DER has no impact on stock returns. ROA cannot moderate the relationship between CR and DER on stock returns. This study can be a reference for companies considering CR and ROA conditions as a support for business decisions. This study contributes ideas for investors to invest in stocks in the automotive and component sub-sectors.